The Sound of Silence Lowest-Noise RIAA Phono-Amps: Designer's Guide - Vogel, Burkhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
There is a wide field of tasks left that can only be satisfyingly attacked with the help of old-fashioned analog technology. One of the most important fields is that of amplifiers for analog signals - such as for audio purposes.   The content of this book will lead to affordable phono amplifier design approaches which will end up in lowest-noise solutions not far away from the edge of physical boundaries set by room temperature and given cartridges - thus, fully compatible with very expensive so called "high-end" or "state-of-the-art" offers on today markets - and, from a noise point of view, in most cases outperforming them!   In this 2nd edition it is demonstrated with easy to follow mathematical treatment that theory is not far away from reality. Measured signal-to-noise ratios of solid-state and valve designs, both alternatively driven by transformers, will be found within 1dB off the calculated ones and deviations from the exact RIAA transfer won't cross the ± 0.1dB tolerance lines. Additionally, the book presents measurement set-ups and results. Consequently, comparisons with measurement results and test approaches of test magazine will be discussed too.
Amps, Pre-Amps, Pre-Pre-Amps -- RIAA Transfer / Anti-RIAA Transfer -- Vinyl Record Reference Levels-.Noise in Components and Other General Noise Effects -- Noise in Bipolar Junction Transistors (BJTs) -- Noise in Field Effect Transistors (FETs) -- Noise in Valves (US: Tubes) -- Noise in Operational Amplifiers (Op-Amps) -- Noise in Instrumentation Amplifiers (In-Amps) -- Noise in Transformers (Trafos) -- Noise of Vinyl Records (VRs) - On how much Phono-Amp SN is Needed? -- Noise Basics - Mathcad Worksheets -- Noise in MM cartridges -- Noise in MM cartridges - Mathcad Worksheets -- Noise in MC Phono-Amps -- Noise in MC Phono-Amps - Mathcad Worksheets -- Noise of Triode Driven Phono-Amps -- Noise of Triode Driven Phono-Amps - Mathcad Worksheets -- RIAA Networks -- RIAA Networks - Mathcad Worksheets.-Measurement System Overview -- Measurement Amps, Noise Generators, FFT Noise Measurements -- Measurement Filters and Networks -- The Hum Figure of Linear Amps -- The Hum Figure of Phono-Amps -- Mathcad Worksheet -- -- Overview -- Modules 1 -4 -- Engine Performance Noise in Components and Other General Noise Effects -- Noise in Bipolar Junction Transistors (BJTs) -- Noise in Field Effect Transistors (FETs) -- Noise in Valves (US: Tubes) -- Noise in Operational Amplifiers (Op-Amps) -- Noise in Instrumentation Amplifiers (In-Amps) -- Noise in Transformers (Trafos) -- Noise of Vinyl Records (VRs) - On how much Phono-Amp SN is Needed? -- Noise Basics - Mathcad Worksheets -- Noise in MM cartridges -- Noise in MM cartridges - Mathcad Worksheets -- Noise in MC Phono-Amps -- Noise in MC Phono-Amps - Mathcad Worksheets -- Noise of Triode Driven Phono-Amps -- Noise of Triode Driven Phono-Amps - Mathcad Worksheets -- RIAA Networks -- RIAA Networks - Mathcad Worksheets.-Measurement System Overview -- Measurement Amps, Noise Generators, FFT Noise Measurements -- Measurement Filters and Networks -- The Hum Figure of Linear Amps -- The Hum Figure of Phono-Amps -- Mathcad Worksheet -- -- Overview -- Modules 1 -4 -- Engine Performance.
Keywords: Signal processing; Image processing; Speech processing systems; Acoustics; Electronic circuits; Electronics; Microelectronics; Signal, Image and Speech Processing; Acoustics; Circuits and Systems; Electronics and Microelectronics, Instrumentation